THE STUDY OF THE NATURE OF THE DEPENDENCE AGEOSTROPHIC WIND SPEED FROM TIME - Robert Gurgenovich Zakinyan; Anastasia Aleksandrovna Zef (Наука. Инновации. Технологии)
This paper examines the nature of the dependence ageostrophic compo-nent of the wind from time to time. The authors made a derivation of the equation, reflecting the dependence of ageostrophic velocity components from time to time. Also calculated the velocity at a given time t. Plotted ageostrophic component of the wind speed from time to time.